Effects of production stages on blending and mechanical properties of asphalt mixtures with reclaimed asphalt pavement. (15th September 2017) - Zhang, Kun; Muhunthan, Balasingam
Highlights: RAP mixtures that underwent different production stages were produced. Diffusion is the most dominant stage that affects properties of RAP mixtures. Thorough mechanical blending improves the ductility of RAP mixtures. Abstract: This study is to investigate the effects of production stages, including RAP binder transfer, mechanical blending, and diffusion, on the blending of RAP and virgin binders and the mechanical properties of RAP mixtures. A laboratory mixing scheme was designed to produce 26 and 50 percent RAP mixtures that underwent a combination of the different production stages. The results show that diffusion is the most dominant stage that affects the rheological and fracture properties of RAP mixtures. On the other hand, thorough mechanical blending contributes to improving the ductility of high percentage RAP mixtures.